Literature study of the influence of exposure factors on receiving radiation doses in radiographic examinations - Novia Anita (Universitas Riau, 2024)
High tube voltage with reduced tube current and exposure time can reduce the dose received by the patient. Based on the principle of optimizing radiation protection and safety, efforts are needed to minimize patient doses in such a way that it still allows for obtaining the necessary diagnostic information. The aim of this study is to investigate whether high tube voltage and lower exposure time can minimize the radiation dose received by patients. This study used a literature review method as the basis for research planning. Literature review involves searching and analyzing various sources of information such as books, journals, and relevant publications to understand the research topic. The research findings indicate that high tube voltage and lower exposure time can minimize the radiation dose received by patients. Therefore, understanding the role of technical factors in radiation dose settings is crucial for medical operators performing X-ray examinations. By selecting the appropriate kVp and mAs settings, it is possible to ensure minimal exposure dose.